Strategi Kepemimpinan Transformasional dalam Meningkatkan Kinerja SDM di Rumah Sakit Umum Daerah Masohi - Hery Siswanto; Gede Pramana Yogi; Purwadhi Purwadhi; Yani Restiani Widjaja (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to describe the transformational leadership strategy implemented in Masohi hospital and analyze its impact on the performance of human resources (HR). The research approach used is qualitative with case study design, which allows researchers to understand the phenomenon in depth in a real context. The Data was collected through in-depth interviews with eight informants, consisting of directors, field heads, room heads, and implementing staff, so that diverse perspectives were obtained from various levels of management and implementers. The data analysis process is carried out through three main stages, namely data reduction, data presentation, and conclusion/verification. The results showed that transformational leadership strategies in Masohi hospital include exemplary, inspirational motivation, innovative thinking encouragement, and attention to individual employee needs. Implementation of this strategy can improve discipline, work ethic, teamwork, and a sense of responsibility of employees in providing services to patients. In addition, it was found that the work culture built through transformational leadership can strengthen organizational commitment and improve overall service quality. However, the implementation of this strategy is not free from challenges. The obstacles that arise include complex bureaucracy, managerial competence gaps between units, as well as resistance to change among staff. This challenge requires an adaptive approach and effective communication so that the strategy can run optimally. Overall, the findings of this study confirm that transformational leadership has a positive impact on strengthening work culture and improving service quality in regional hospitals. This research is expected to be a valuable input for the development of leadership and HR management policies, not only in Masohi hospital, but also in other regional hospitals that face similar challenges.